Biological corneal inlay for presbyopia derived from small incision lenticule extraction (SMILE) - Liu, Yu-Chi (2018)
Corneal inlays are a relatively new treatment option for presbyopia. Using biological inlays, derived from lenticules extracted from small incision lenticule extraction, may offer advantages over commercialized synthetic inlays in the aspect of biocompatibility. We conducted a non-human primate study to evaluate the safety, predictability, efficacy and tissue response after autogeneic, decellularized xenogeneic and xenogeneic lenticule implantation. The lenticule implantation effectively resulted in central corneal steepening (simulated keratometric values increased by 1.8–2.3 diopters), central hyper-prolate changes (asphericity Q values changed by −0.26 to −0.36), corneal anterior surface elevation (7.7–9.3 μm) and reasonable effective zone (1.5–1.8 times of the lenticule physical diameter), with no differences among the three groups. Slit lamp microscopy, transmission electron microscopy, confocal microscopy, histology and immunohistochemistry analyses confirmed the biocompatibility of the autogeneic and decellularized lenticules, whereas one eye in the xenogeneic group developed corneal stromal rejection during the study period. Our results showed that lenticule implantation has the potential for the management of presbyopia, and provide the basis for future clinical studies. The decellularization process may increase the potential utilization of lenticules without changing the efficacy.